The Common Component Modeling Example - Herold, Sebastian (Springer, 2017)
The example of use which was chosen as the Common Component Modeling Example (CoCoME) and on which the several methods presented in this book should be applied was designed according to the example described by Larman in [1]. The description of this example and its use cases in the current chapter shall be considered under the assumption that this information was delivered by a business company as it could be in the reality. Therefore the specified requirements are potentially incomplete or imprecise.